Review of toxicity studies of carbon nanotubes - Kobayashi, Norihiro (J Occup Health, 2017)
OBJECTIVE: We reviewed studies on pulmonary, reproductive, and developmental toxicity caused by carbon nanotubes (CNTs). In paricular, we analyzed how CNT exposure affects the several processes of pulmonary toxicity, including inflammation, injury, fibrosis, and pulmonary tumors. METHODS: In pulmonary toxicity, there are various processes, including inflammation, injury, fibrosis, respiratory tumor in the lungs, and biopersistence of CNTs and genotoxicity as tumor-related factors, to develop the respiratory tumor. We evaluated the evidence for the carcinogenicity of CNTs in each process. In the fields of reproductive and developmental toxicity, studies of CNTs have been conducted mainly with mice. We summarized the findings of reproductive and developmental toxicity studies of CNTs. RESULTS: In animal studies, exposure to CNTs induced sustained inflammation, fibrosis, lung cancer following long-term inhalation, and gene damage in the lung. CNTs also showed high biopersistence in animal studies. Fetal malformations after intravenous and intraperitoneal injections and intratracheal instillation, fetal loss after intravenous injection, behavioral changes in offsprings after intraperitoneal injection, and a delay in the delivery of the first litter after intratracheal instillation were reported in mice-administered multi-walled carbon nanotubes (MWCNTs). Single-walled carbon nanotubes (SWCNTs) appeared to be embryolethal and teratogenic in mice when given by intravenous injection; moreover, the tubes induced death and growth retardation in chicken embryos. CONCLUSION: CNTs are considered to have carcinogenicity and can cause lung tumors. However, the carcinogenicity of CNTs may attenuate if the fiber length is shorter. The available data provide initial information on the potential reproductive and developmental toxicity of CNTs.